Where the girls are: trade and labor market segregation in Colombia - Josh Ederington; Jenny Minier; Kenneth R. Troske (Institute for the Study of Labor (IZA), 2009)
Gary Becker's theory of discrimination argues that increasing competition will reduce discrimination in the labor market. We use the Colombian trade liberalization episode over the period 198491 to investigate this claim on plant-level data in three ways. First, we examine whether women are concentrated in exporting plants. Second, we examine whether the increase in foreign competition due to unilateral trade liberalization disproportionately drove discriminating plants out of the market. Finally, we investigate whether trade liberalization affected hiring decisions (and thus gender segregation) by Colombian firms.
urn:nbn:de:101:1-20090513294
Keywords: J7; 330; Discrimination; trade; competition; Arbeitsmarktdiskriminierung; Geschlechterdiskriminierung; Außenhandelsliberalisierung; Internationaler Wettbewerb; Kolumbien